Finding Optimal Location Development UPPKB In South Sumatera Province Using Multi-Criteria Analysis - Priambudi, Bagus Nuari; Ariani, Nofa Martina; Hadi Wijaya, Muhammad Indra (Jurnal Transportasi Multimoda, 2023)
The distribution of commodity transportation is a crucial factor for the sustainability and continuity of economic activities in specific regions. Shipments occur daily, especially on main roads, with the majority of goods transported exceeding tonnage limits when passing through roads. If this continues without control and security measures, it will lead to a deterioration of the physical quality of the road, disrupting the distribution of goods transportation. The Vehicle Weighing Station (UPPKB) is a form of control and security implemented by the government to regulate the transportation of goods distribution above tonnage limits. Every day, the transportation of goods distribution in South Sumatera Province is significant due to its numerous power plants and tourist destinations. This research aimed to identify the location for the development of UPPKB using a quantitative method to obtain indicators for multi-criteria analysis. The conclusion drawn from the identified potential points indicates positive results, making it feasible to construct a new UPPKB at those locations. The potential locations for the development of a new UPPKB in South Sumatera are Betung 1 Street and Yusuf Singadekane 1 Street